The Impact of GHRM Practices on Employee Performance Mediated by Innovative Work Culture (A Study in PT Bank Kalteng, Indonesia) - Santi, Emelia (International Journal of Review Management Business and Entrepreneurship (RMBE), 2023)
The study aimed to determine the impact of green human resource management (GHRM) practices on employee performance and innovation within Indonesia's banking sector. By investigating the relationships between green knowledge sharing, innovative work culture, and employee performance, the research sought to understand how the implementation of GHRM initiatives could drive sustainable practices, enhance organizational effectiveness, and foster a culture of innovation. The variables studied included green knowledge sharing, innovative work culture, and employee performance. The study respondent comprised 150 employees from the PT Bank Kalteng, selected using purposive sampling. Data collection was conducted through an online questionnaire utilizing a 1–5 Likert scale. A quantitative approach was employed to investigate the impact of GHRM practices on employee performance and innovation in the banking sector. Data processing methods, such as the use of SMART-PLS 3 for structural equation modeling (SEM) analysis, were utilized. The results revealed significant findings regarding the impact of GHRM practices on employee performance and innovation in Indonesia's banking sector. Green Knowledge Sharing (GKS) exhibited a positive and statistically significant relationship with employee performance, while Innovative Work Culture (IWC) also demonstrated a positive and significant relationship with employee performance. Additionally, the indirect influence test results indicated that green knowledge sharing (GKS) significantly influenced employee performance through innovative work culture, suggesting that fostering a culture of innovation mediated the relationship between green knowledge sharing (GKS) and employee performance (EP). These findings offer valuable insights into the role of GHRM initiatives in promoting environmental sustainability, enhancing organizational effectiveness, and supporting a culture of innovation in the banking industry.